1991
DOI: 10.1016/s0022-5347(17)38512-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function following Radical Prostatectomy: Influence of Preservation of Neurovascular Bundles

Abstract: The influence of preservation or excision of the neurovascular bundles on return of sexual function is analyzed. Between 1982 and 1988, 600 men 34 to 72 years old underwent radical retropubic prostatectomy for prostate cancer. Of the 503 patients who were potent preoperatively and followed for a minimum of 18 months 342 (68%) are potent postoperatively. Three factors were identified that correlated with the return of sexual function: 1) age, 2) clinical and pathological stage, and 3) surgical technique (preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
2
17

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(211 citation statements)
references
References 14 publications
5
183
2
17
Order By: Relevance
“…Previous animal studies by Quinlan et al and Ball et al using the genitofemoral nerve demonstrated the ability of interposition nerve grafts to recover erectile function in the majority of denervated rats, as measured by mating studies and electric pelvic nerve stimulation. 3,21 Improvement of erectile function was noted at 3 -4 months postoperatively. In humans, however, the procedure is technically more challenging, since the cavernous nerve is not a well-defined structure, but consists of multiple nerves, which are dispersed in a plexus surrounded by vessels.…”
Section: Discussionmentioning
confidence: 93%
“…Previous animal studies by Quinlan et al and Ball et al using the genitofemoral nerve demonstrated the ability of interposition nerve grafts to recover erectile function in the majority of denervated rats, as measured by mating studies and electric pelvic nerve stimulation. 3,21 Improvement of erectile function was noted at 3 -4 months postoperatively. In humans, however, the procedure is technically more challenging, since the cavernous nerve is not a well-defined structure, but consists of multiple nerves, which are dispersed in a plexus surrounded by vessels.…”
Section: Discussionmentioning
confidence: 93%
“…The reported potency rates after bilateral nerve-sparing RP in most series varies from 53 to 86%. 4,5,7,8 The current dilemma acknowledging ED following RP is due to wide variation in the potency rates reported in the literature. This variation appears to be dependent not only on the above variables, but also may be due to nonuniformity in data collection.…”
Section: Ed After Rpmentioning
confidence: 99%
“…Five-year potency rates after prostate cancer treatment with radical prostatectomy, EBRT and implantation are approximately 40%, 75% and 80%, respectively. 15,17,18 These data suggest that brachytherapy is the best method for prostate cancer treatment from a quality-of-life viewpoint. Our characterization of sexual function with the International Index of Erectile Function (IIEF 15) and nocturnal penile tumescence (NPT) demonstrated that all patients who had undergone brachytherapy using LDR Ir-192 were able to preserve their potency, and 66% maintained their pretreatment ability.…”
Section: Complicationsmentioning
confidence: 99%